2018
DOI: 10.1073/pnas.1802254115
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-independent role of NPR1 is required for protection from proteotoxic stress in the plant endoplasmic reticulum

Abstract: The unfolded protein response (UPR) is an ancient signaling pathway designed to protect cells from the accumulation of unfolded and misfolded proteins in the endoplasmic reticulum (ER). Because misregulation of the UPR is potentially lethal, a stringent surveillance signaling system must be in place to modulate the UPR. The major signaling arms of the plant UPR have been discovered and rely on the transcriptional activity of the transcription factors bZIP60 and bZIP28 and on the kinase and ribonuclease activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 69 publications
3
50
0
1
Order By: Relevance
“…The role of these inducers in long-distance ER stress signaling is yet to be evaluated and it is conceivable that long-distance ER stress signaling may overlay a bZIP60-mediated signaling with the action of other stress transducers. Nonetheless, it has been shown in seedlings that ER stress responses are independent from endogenous SA and that Tm does not induce accumulation of SA 52 . Therefore, long-distance ER stress signaling is likely independent from SA.…”
Section: Discussionmentioning
confidence: 99%
“…The role of these inducers in long-distance ER stress signaling is yet to be evaluated and it is conceivable that long-distance ER stress signaling may overlay a bZIP60-mediated signaling with the action of other stress transducers. Nonetheless, it has been shown in seedlings that ER stress responses are independent from endogenous SA and that Tm does not induce accumulation of SA 52 . Therefore, long-distance ER stress signaling is likely independent from SA.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction mechanisms of ISR remain poorly understood. It has been confirmed that salicylic acid pathway (SA), ethylene pathway (ET) and the jasmonic acid (JA) are different regulatory pathways, and act as core candidates in the signaling system, as well as in the defense response ( Lai et al, 2018 ; Pieterse and van Loon, 1999 ; Zhang et al, 2018a ). SA is considered to be the most prominent signaling molecule having a key role in system resistance as well as local defense reactions ( Glazebrook, 2001 ).…”
mentioning
confidence: 99%
“…Furthermore, some level of oxidative stress due to H 2 O 2 production is intrinsic to disulfide bond formation in the ER (Harding et al, 2003). An overloaded ER that is not able to sufficiently correct and resolve misfolded proteins can result in H 2 O 2 production significant enough to alter the glutathione redox state (Ozgur et al, 2014;Dietz et al, 2016) and to influence the cytosolic redox potential (Lai et al, 2018). Therefore, in the context of an overloaded ER protein folding machinery, it might be adaptive to specifically downregulate expression of SSPs with very high S-AA density, such as S-rich 10kDa prolamin (Hagan et al, 2003), so that cysteine could then be repurposed for GSH synthesis.…”
Section: Discussionmentioning
confidence: 99%